1999
DOI: 10.1007/s11894-996-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract inflammatory disorders: Primary sclerosing cholangitis and primary biliary cirrhosis

Abstract: Primary sclerosing cholangitis (PSC) and primary biliary cirrhosis (PBC) are chronic progressive cholestatic diseases that frequently lead to biliary cirrhosis. The exact pathogenesis of these diseases remains elusive but is likely immunologically based. Complications range from fatigue and pruritus to end-stage liver disease. The risk of developing hepatocellular carcinoma is low for patients with PBC, whereas cholangiocarcinoma is common in PSC and carries an ominous prognosis. Although ursodeoxycholic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…BDC is relatively uncommon, but one of the worst prognostic cancers in abdominal neoplasm. 36,37 Clinical and patholog-ical evidence has suggested that inflammatory conditions involving the bile ducts predispose these ducts to the development of BDC, [39][40][41][42][43][44][45]72 however, the relationship between chronic inflammation and malignant transformation remains unclear. Recently, in many tumors, COX-2 overexpression has been suggested to play an important role in both carciogenesis and increased malignant potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BDC is relatively uncommon, but one of the worst prognostic cancers in abdominal neoplasm. 36,37 Clinical and patholog-ical evidence has suggested that inflammatory conditions involving the bile ducts predispose these ducts to the development of BDC, [39][40][41][42][43][44][45]72 however, the relationship between chronic inflammation and malignant transformation remains unclear. Recently, in many tumors, COX-2 overexpression has been suggested to play an important role in both carciogenesis and increased malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…Although both epithelial cells were accompanied with various levels of inflammation, only PSC has the high risk for cholangiocarcinoma (IHBC). [39][40][41] Bile duct epithelial cells in PSC showed higher levels of COX-2 protein, comparable with those in BDC, and these high-level expressions of COX-2 were observed regardless of inflammatory reaction around them. On the other hand, epithelial cells in PBC showed positive staining of COX-2, but the staining levels were moderate, and the expression levels were comparable with those of bile duct epithelial cells in inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study also showed that PGE 2 and PGF 2α irectly stimulated the proliferation of a cholangiocarcinoma cell line (5). Furthermore, it is well known that inflammatory and cholestatic conditions of the liver (e.g., PSC, biliary stone disease, and Caroli's disease) predispose patients to the development of biliary tract carcinoma (6)(7)(8)(9)(10)(11). These reports suggest that COX-2 and cytotoxic bile acids are closely related to the development of biliary tract carcinoma.…”
mentioning
confidence: 92%